Robust adaptive dynamic programming for linear and nonlinear systems: An overview - Jiang, Zhong-Ping; Jiang, Yu (European journal of control, 2013)
The field of adaptive dynamic programming with diverse applications in control engineering has undergone rapid progress over the past few years. A new theory called “Robust Adaptive Dynamic Programming” (for short, RADP) is developed for the design of robust optimal controllers for linear and nonlinear systems subject to both parametric and dynamic uncertainties. A central objective of this paper is to give a brief overview of our recent contributions to the development of the theory of RADP and to outline its potential applications in engineering and biology.